Metodo e strategie di studio: cosa sanno gli studenti? Un'indagine all'Università di Trento - Veronica Cembrani; Anna Serbati; Claudio Mulatti (LED Edizioni Universitarie, 2023)
Study Methods And Learning Strategies: What Do Students Know? A Survey At The University Of Trento. How do students study? What do students know about study methods and learning strategies? Recent research has shown that most students rely on ineffective study methods. This behavior could be ascribed to a limited knowledge about learning strategies: students might rely on ineffective study methods because they have erroneous views about which learning strategies are effective. The aim of our research has been to further address this topic at the University of Trento. Here, we present and discuss the results of a survey study that investigates the students' knowledge of some common learning strategies, the beliefs about their utility, and how much students intended to use them during the semester. Our results confirm that students are often not aware of which learning strategies are most effective. Furthermore, our data suggests that even when students do know how they should study, they do not always reflect it in their study activities. These conclusions requires appropriate considerations and intervention in educational contexts.